(untitled) (American Journal of Business Management, Economics and Banking, 2024)
In recent years, e-commerce and marketplaces have created new opportunities for small businesses. Small businesses are an important component of the economy, and their development greatly affects the economic stability and social well-being of countries. This article analyzes the role of e-commerce sites and marketplaces in the development of small businesses in Uzbekistan.